FAO technical guidelines for responsible fisheries N4: Fisheries management - FAO (FAO, 1996)
The Guidelines provide a background to be need for fisheries management and an introduction to the activities encompassed by fisheries management. They introduce the major constraints exprienced in fisheries and fisheries management and some of the fundamental concepts related to these. Biological, environmental, technological, socio-cultural and economic constraints and concepts are examined.